Information and awareness-raising on natural disasters among young university students from Madrid. Expert opinion - García Nieto, María Teresa; Ibarz Moret, Ana; Sánchez Antúnez, Rosalía; Santamaría Gutiérrez, Sara; Tapia Mayer, Andrea (Revista Española de Comunicación en Salud, 2019)
In the world, natural disasters have increased greatly during the last decade, which has resulted in a significant increase in victims and material damage. Currently, approximately 70% of these disasters are related to climate, twice as many as 20 years ago, according to the UN. In the case of Spain, scientists agree that the most frequent are floods and overflows. Although the country enjoys an auspicious scenario in comparison with other countries with more catastrophes, this also generates an inconvenience: the population, and especially the young people, do not have a social conscience about natural disasters and would not know how to act in case of an emergency, premise that constitutes the main hypothesis of this investigation. Therefore, the primary objective of knowing the level of information and awareness that the young Spanish population has about natural disasters and to be able to develop the final objective of combating this problem by generating more education and information about it.